The impact of urban morphology and building's height diversity on energy consumption at urban scale. The case study of Dubai. (May 2021) - Shareef, Sundus
Abstract: The indoor air temperature and cooling load are highly affected by the surrounding environment. Enhancing outdoor thermal performance leads to a positive impact on energy consumption for cooling purposes, specifically in hot climate countries such as the UAE. The UAE weather characteristics specified as desert climate, however, it is more humid than the other cities with similar climate conditions. It has been found that a limited number of publications concern with the direct impact of urban morphology on the indoor cooling load within local climate conditions of the UAE. Moreover, the integrated and direct impact of height diversity on the indoor cooling load at an urban scale requires more investigation. This study aims to explore the impact of urban morphology, specifically height diversity on the cooling load within local climate conditions of the UAE. Furthermore, it aims to find an optimized cooling consumption prototype of an urban block to emphasize the study novelty. It adopts urban planning and building morphology to optimize the outdoor thermal performance and reflect this enhancement on indoor energy consumption. The results show that the orientation is the most influential factor in the urban block cooling load and energy consumption. It is significantly and directly control the amount of solar radiation and buildings solar gain. The minimum direct solar gain of the base case configuration concerning the orientation is recorded in the N–S with a reduction of 13% compared to the NE-SW orientation. This has resulted in a reduction in cooling load by 6.4% between these two orientations. Further to that, the reduction in outdoor air temperature and solar gain by implementing the building's height diversity resulted in a reduction in cooling load by 4.6% between the base case and the urban block configuration with the building's height diversity. Graphical abstract: Image 1 Highlights: The impact of height diversity on outdoor microclimate parameters. The integration of changes in microclimate parameters to indoor energy consumption. IES-VE and ENVI-Met 4.4.3 simulation software. Cooling load and the contribution of solar gain and conduction gain in total heat gain. Reduction in cooling load by 6.4% due to orientation and 4.6% due to height diversity implementation.